A Historical Review of Data and Information of Indonesian Mangroves Area - Aswin Rahadian; Lilik Budi Prasetyo; Yudi Setiawan; Ketut Wikantika (Media Konservasi, 2019)
Quantification of the mangrove area in Indonesia was very diverse, which is quantified in the pre and post development of remote sensing technology. This causes uncertainty comprehensive information of mangrove in Indonesia. The planners at national and international level of faced with the problems of uncertainty information that has implications for the quality of data availability. Therefore, it is important to develop a comprehensive of mangrove extent and distribution database. The method used in-depth study literature on various publications related mangrove mapping in Indonesia and comparative analysis. This study aims to identify comprehensive information mangrove forests of Indonesia and analyze the factors which cause diversity of quantification area and reliability of data. We found 42 publications containing data and information on Indonesia's mangrove forests area, with 17 sources including detailed information per province. The study results showed that the difference mangrove quantification area was influenced by several main factors including analysis periode, differences in the concept and mangrove boundaries, basic data and scale, method of mangrove mapping, as well as regional coverage. Keywords: historical data, Indonesia, mangrove area